Removal of Safranin Dye from Aqueous Solution using Surfactant-Modified Carbonized Olive Stones - Umar, Mausul (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
The adsorption study of safranin dye by surfactant modified carbon MCOS produced from olive stone under batch adsorption process was undertaken to check the influence of varying different experimental conditions; initial safranin concentration, pH, adsorbent dosage, temperature, counter ions and time on safranin removal by our adsorbent. Physiochemical characterizations including moisture content, ash content, bulk density etc. was also undertaken. Two well known adsorption isotherms (Langmuir and Freundlich) and three kinetic models (pseudo first and second order, intra particle diffusion) were used to better understand the mechanism involved in the adsorption process. Our collected results showed that there was an increase in adsorption capacity of MCOS as initial dye concentration, dose and number of counter ions in solution increased; pHpzc was at pH 6.6 while maximum adsorption capacity was 7.30mg/g obtained at pH 7. Langmuir isotherm which implies monolayer coverage by MCOS well represented our equilibrium data with a higher correlation coefficient value of while kinetic study showed that adsorption process followed pseudo second order kinetic model. RL and n values obtained from both adsorption isotherms used indicates a favorable adsorption process. The spontaneity and exothermic nature was confirmed by negative ΔG° and ΔH° values, though spontaneity reduced as temperature increased. Hence, MCOS can serve as an ecofriendly and cheap alternative for removing safranin from industrial waste effluents.

ÖZ: Safran boyasının yüzey aktif madde modifiye edilmiş karbonize zeytin çekirdeği MCOS tarafından emilimi üzerine yapılan çalışmada, başlangıçtaki safran konsantrasyonu, pH değeri, emici dozajı, sıcaklık, karşı iyonlar ve safranın kullandığımız emici tarafından adsorbe edilmesi için gereken süre gibi deneysel koşulların adsorpsiyon üzerindeki etkisi kontrol edilmiştir. Nem içeriği, kül içeriği, yığın yoğunluğu gibi fizyokimyasal nitelemeler de üstlenmiştir. Adsorpsiyon işleminin mekanizmasını daha iyi anlayabilmek içi, iki iyi bilinen adsorpsiyon izotermi (Langmuir ve Freundlich) ve üç kinetik modeli (yalancı birinci ve ikinci dereceden, partikül içi difüzyonu) kullanılmıştır. Elde edilen sonuçlar; başlangıçtaki boya konsantrasyonu, çözeltideki doz ve karşıt iyon sayısı arttıkça, MCOS'un adsorpsiyon kapasitesinde bir artış olduğunu göstermiştir; pH değeri 7 iken, maksimum adsorpsiyon kapasitesi 7.30mg / g olarak elde edilmiş, ve pHpzc değerinin pH 6.6 olduğu gözlemlenmiştir. Bu çalışmada, adsorpsiyon prosesinin yalancı ikinci dereceden kinetik modeli izlediğini göstermekle birlikte, MCOS tarafından tek katmanlı kapsama alanını ifade eden Langmuir izotermi, denge verilerimizin daha yüksek bir korelasyon katsayısı değeri ile temsil edildimiştir. Kullanılan her iki adsorpsiyon izoterminden elde edilen RL ve n değerleri, elverişli bir adsorpsiyon olayını gösterir. Sıcaklık arttıkça spontaneliğin azalmasına rağmen, spontanelik ve ekzotermiklik, negatif ΔG ° ve ΔH° değerleri ile teyit edilmiştir. Bu nedenle, MCOS, endüstriyel atık çıkışlarından safran giderimi için çevre dostu ve ucuz bir alternatif olarak hizmet verebilir.
Master of Science in Chemistry. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Chemistry, 2017. Supervisor: Assoc. Prof. Dr. Mustafa Gazi.
Keywords: Safranin; activated carbon; adsorption; olive stones; Chemistry